(untitled) (Economic and Political Thought, 2018)
The article discusses the issues of social function and responsibility of a higher education institution in its direct local surroundings. Universities operating in medium size and small towns are the point of reference so they are mainly non-public universities and state-owned higher vocational schools. The choice is justified by the fact that apart from their educational activity, they create local elites and remain culture-creating centres. Their educational offer is determined by the local community needs, which means that the paths of training and their level express the scope of a higher education institution’s responsibility for the development of human capital, the region, competitiveness and attractiveness of the local labour market.